SOCIAL-PSYCHOLOGICAL PECULIARITIES OF CONSUMER’S BEHAVIOR - Kulchytska, Anna V. (Psychological Prospects Journal, 2017)
This article is dedicated to the investigation of consumer’s personal behavior. The author has proved the topicality, conducted the research analysis of this problem, and defined the investigative methods and the methodology of social-psychological personal characteristics and peculiarities of consumer’s behavior. The research topicality is determined by booming development of society and economics, necessity of solution of scientific targets, the centre of which is a human as a subject of economic activities. One of such questions is the investigation of consumer’s behavior and factors, which have influence on it. The author assumes the view that consumer’s behavior does not reduce only to maximization of usefulness, rational scores and calculations. Moreover, besides the functional demand on goods, there is also non-functional demand, which is caused by different, including psychological factors. The article shows the results of quantative and qualitative analysis. The article has found out personal individual-psychological characteristics using Multifactorial personality questionnaire of R. Kettle. The diagnostics results are represented according to sixteen figures. In article there are represented research results of psychological types of customer’s behavior according to the methodology of O. S. Posypanova “Psychological profile of customer”. Even profiles of customers have been determined and described: innovator, fashioner, traditionalist, conservator, individualist, situationalist, careless. According to diagnostics results with the help of correlating analysis there have defined interconnection peculiarities of personal individual and psychological characteristics and customer’s behavior elements, which are definite in customer’s psychological profiles typology. In this article there are also the prospective of the following investigations. Key words: customer’s behavior, individual and psychological personal characteristics, customer’s psychological profile.